Comparison of The Pull Strength of Sisal Lamina Matrix Polymer Fiber Composite Materials (Agave Sisalana) - Fikran, FIkran; Simon, Christof Geraldi; ka’ka, Simon (Politeknik Negeri Ujung Pandang, 2023)
Composites are one of the material engineering technologies developed today because composites can combine several material properties that differ in characteristics into new properties by the planned design. The purpose of this study was to determine the mechanical properties of the influence of the combined arrangement of lamina angle variations and the composition of fiber and matrix mixtures. This study uses polyester resin, catalyst, and sisal fiber as materials in the manufacture of composite materials. In specimen manufacturing refers to ASTM D 638-02 type 3 test standard for tensile tests. The tensile test results of sisal fiber lamina composite materials assuming a composition ratio of 5% fiber and 95% resin produce maximum tensile stress of m = 16.9854 N/mm2 and a maximum strain of É› = 4.5232% while assuming a composition ratio of 15% fiber 85% resin produces maximum tensile stress of sm = 40.1422 N/mm2 and maximum strain of É› = 8.9744 %, Based on the test results, the addition of fiber mixture composition increases the tensile strength and toughness of the material. The composition of 5% fiber 95% and 15% fiber 85% resin (15S-85R)produces a maximum tensile stress of sm = Â 45.1823 N/mm2 and a maximum strain of É› = 9.6849 % with a maximum load Fm = 10902.4996 N. The more fiber contained in the sisal fiber lamina composite material, the higher the tensile stress produced, this shows the tension is directly proportional to the number of fibers contained in the composite.